On line Bromimetric Determination of Sulphonamides Using Flow Injection with Chemiluminescence Detection - Bahan, Shirwan Omer; Shawket, Sirwan Fadhil (Sulaimani Journal for Pure and Applied Sciences, 2001)
Organic compounds that can be brominated by bromine are determined by injection them in acidic solution into bromate-bromide eluent. Unconsumed bromine was monitored using [BrrH2O2-Luminol] chemiluminesence system. The optimum parameters were studied and were found to be the following: KBr 0.2 Al, KI3r03 0.1M, CH3COOH 1M, H202 0.01 M, Luminol 5x10' M, flow rate 3.5 ml mfri 1, and 100 pl sample with frequently of 90K', gave working rang‘s of 10-70 pg , with precision less than 2%. Detection limits of down to 10 ng per 100 pl sample were obtained Application to a methoprim tablet was described.
Keywords: Chemiluminesece Detection Flow Injection Sulphonamides Determination Lumina